2000
DOI: 10.1002/1529-0131(200005)43:5<988::aid-anr5>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of progressive joint space narrowing in osteoarthritis of the hip: Longitudinal analysis of the contralateral hip after total hip arthroplasty

Abstract: Radiographic hip JSW may be reliably quantified and followed up longitudinally using standard AP radiographs. Progression of JSW narrowing in the contralateral hip after THA for OA proceeds in a linear manner over several years. A subpopulation of patients with accelerated narrowing of contralateral JSW may be identified within 20 months, and may represent a suitable population with which to assess the potential efficacy of new disease-modifying agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 15 publications
5
43
0
Order By: Relevance
“…We found a 71% decrease in the risk of change to Charnley Class B for each 1-mm increment (Table 1). This result correlates the findings of some authors who showed associations of joint space width with development of symptoms or the need for hip arthroplasty [2,4,10]. However, the finding of an eccentric joint space showed just as strong an association with the change to Charnley Class B as the minimum joint space width in a preliminary bivariate analysis (HR, 12; p = 0.001).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found a 71% decrease in the risk of change to Charnley Class B for each 1-mm increment (Table 1). This result correlates the findings of some authors who showed associations of joint space width with development of symptoms or the need for hip arthroplasty [2,4,10]. However, the finding of an eccentric joint space showed just as strong an association with the change to Charnley Class B as the minimum joint space width in a preliminary bivariate analysis (HR, 12; p = 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…This could be because a substantial number of hips in our cohort were included because they showed no symptoms at baseline evaluation but already had indicators that the osteoarthritic process was engaged. Similarly, Goker et al [10] noted a 21% rate of hip arthroplasty performed during the course of their study. These survivorship results also are consistent with the findings of Vossinakis et al [20], who reported an increased risk of development of contralateral OA in patients with idiopathic OA in one hip, and the results of Clohisy et al [3], who found a high prevalence of structural abnormalities consistent with femoroacetabular impingement in patients with idiopathic OA and a high rate of subsequent contralateral THA.…”
Section: Discussionmentioning
confidence: 72%
“…Both, intrarater and interrater reliability has been significantly higher for joint space measurement than for Kellgren and Lawrence scoring (10,27), and the findings that decline of JSW in OA proceeds in a linear manner (28) and that JSW is predictive of long-term progression of joint-space narrowing (29) make measurement of JSW suitable for clinical trials and prioritize the identification of genes responsible for cartilage formation and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In one study evaluating the probability of contralateral THAs in 99 patients with a mean followup of 104 months (range, 12-149 months), after excluding patients undergoing contralateral THA within 12 months of index THA, the risk of contralateral THA was reportedly 21% [10].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with bilateral disease, the chance of subsequent contralateral THA after unilateral THA is anywhere from 16% to 85% [10,12,[19][20][21][22]. Factors related to subsequent joint arthroplasty in the contralateral joint are described as the radiographic grade of the joint [10,21] and patient age [17,21] at index arthroplasty. Although there is a study regarding the degree of radiographic OA and patient age [21], it does not evaluate symptoms in the contralateral hip and correlate this with radiographic grading in the contralateral hip at index THA.…”
Section: Introductionmentioning
confidence: 99%